2015
DOI: 10.1007/s11242-015-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Helical Flow and Transient Solute Dilution in Porous Media

Abstract: Artículo de publicación ISIHelical flow can occur in porous media if the hydraulic conductivity tensor is anisotropic.We study the structure of steady-state flowfields in three-dimensional anisotropic porous media formed by two homogeneous layers, one of which is anisotropic.We simulate transient transport of a conservative scalar in such flowfields by a hybrid streamline/smoothed particle hydrodynamics method and analyze dilution. We use stretching and folding metrics to characterize the flow field and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Since the mixing behavior is highly dependent on the flow field [8,9,16,45], the flow field in a single rough fracture was solved directly by using the Navier-Stokes and continuity equations for isothermal, incompressible, and homogenous single Newtonian steady flow:…”
Section: Computational Fluid Dynamics (Cfd) Simulations Of the Flow Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the mixing behavior is highly dependent on the flow field [8,9,16,45], the flow field in a single rough fracture was solved directly by using the Navier-Stokes and continuity equations for isothermal, incompressible, and homogenous single Newtonian steady flow:…”
Section: Computational Fluid Dynamics (Cfd) Simulations Of the Flow Fmentioning
confidence: 99%
“…This indicates that the spatial distribution of local apertures and the corresponding spatial changes in velocity have a significant influence on the temporal evolution of the SDR. Since mixing is the only process of solute mass exchange between the different streamlines, the distribution of streamlines significantly impacts the mixing [8]. In the constant-aperture fracture, the streamlines are uniform over the entire fracture, whereas the streamlines in the variable-aperture fracture are deformed and bent due to the spatial distribution of local apertures (see Figure 4).…”
Section: Influence Of the Roughness Of Fracture Walls On The Temporalmentioning
confidence: 99%
See 1 more Smart Citation
“…For the heterogeneous system, the flow velocity distribution in the porous media is a fundamental issue for understanding the mixing behavior of solute plume [21]. As the mixing process is highly influenced by the flow field [22,23], molecular diffusion causes the solute molecule movement between streamlines and enhances mixing. Some recent studies characterized topological [24] and kinematic [25] features of the flow field to explore the influence of the flow field on the mixing behavior of the solute plume.…”
Section: Introductionmentioning
confidence: 99%
“…In modeling studies in three-dimensional anisotropic porous media, Hemker et al (2004), Hemker and Bakker (2006) and Stauffer (2007) showed the existence of whirling streamlines which can considerably affect solute transport. The link between complex three-dimensional flow topology in heterogeneous anisotropic porous media and mixing has been addressed in a few recent modeling works (Bennet et al 2017;Chiogna et al 2014Chiogna et al , 2015Chiogna et al and 2016Cirpka et al 2015).…”
Section: Introductionmentioning
confidence: 99%